Plan estratégico de marketing para la empresa “Jiménez & Jiménez, distribución y venta de productos de primera necesidad” en la ciudad de Zaruma. - Toro Toro, Andrea Del Cisne (2022)
At the present times, the business potential has increase significantly since they seem to be forced to using technological tools through marketing strategies, in consequence to the global pandemic called “COVID-19”. Thanks to that, the local, national and global economy has been affected in different sectors, which is why this research work titled "Strategic marketing plan for the Jiménez &Jiménez company" in charge of the distribution and sale of basic needs products in the city of Zaruma. To carry out this research, it was used the deductive, analytical and synthetic methods. Furthermore, different techniques such as; an interview to the manager and a survey to the clients, were applied to get the necessary data for the research. In addition to that, there is the external analysis, in which, economic, technological, political, ecological and legal factors were presented, complemented by Porter’s analysis of the five forces, the EEF matrix (Evaluation of External Factors) was proposed, where 2.70 of the result was obtained, which means threats are taking precedence over opportunities. Meanwhile in the matrix of valuation of internal factors, a value of 3.05 was obtained. This means, strengths are taking precedence over weaknesses, which means that the Company is well positioned in the market.